2017
DOI: 10.3389/fimmu.2017.00241
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection and Compromised Mucosal Immunity: Oral Manifestations and Systemic Inflammation

Abstract: Mucosal surfaces account for the vast majority of HIV transmission. In adults, HIV transmission occurs mainly by vaginal and rectal routes but rarely via oral route. By contrast, pediatric HIV infections could be as the result of oral route by breastfeeding. As such mucosal surfaces play a crucial role in HIV acquisition, and spread of the virus depends on its ability to cross a mucosal barrier. HIV selectively infects, depletes, and/or dysregulates multiple arms of the human immune system particularly at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 195 publications
3
72
0
5
Order By: Relevance
“…While viral replication is effectively suppressed with ART, systemic inflammation persists from cell‐to‐cell viral transfer, microbial translocation of bacteria and viral co‐infections such as cytomegalovirus (CMV) and herpes simplex virus (HSV) (reviewed in ). Because microbial translocation of proinflammatory bacterial products drives systemic inflammation , we postulated that this may activate the complement cascade. Thus, we sought to determine if sMAC levels were altered in ART‐treated, virally suppressed PLWH (ART‐VS‐PLWH) due potentially to pathogen by‐product‐mediated complement activation.…”
Section: Resultsmentioning
confidence: 99%
“…While viral replication is effectively suppressed with ART, systemic inflammation persists from cell‐to‐cell viral transfer, microbial translocation of bacteria and viral co‐infections such as cytomegalovirus (CMV) and herpes simplex virus (HSV) (reviewed in ). Because microbial translocation of proinflammatory bacterial products drives systemic inflammation , we postulated that this may activate the complement cascade. Thus, we sought to determine if sMAC levels were altered in ART‐treated, virally suppressed PLWH (ART‐VS‐PLWH) due potentially to pathogen by‐product‐mediated complement activation.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that these biomarkers can be used to predict which patients will have progressive disease (Tomas et al, 2017). Unfortunately, more advanced periodontal disease is common in adults with HIV (Heron & Elahi, 2017;Ryder, Nittayananta, Coogan, Greenspan, & Greenspan, 2012). Since little is known regarding PHIV youth and biomarkers of disease progression, follow-up of this cohort will be essential and is currently underway.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with Dang et al, 2012, who also showed an impact of the HIV-1 infection on the dorsal tongue microbiota, albeit in untreated HIV-1-infected adults. The effect of HIV-1 infection in the subgingival and tongue sites could be associated with the CD4+ T-cell depletion and consequence decrease of T-cell-associated cytokines, including IL-17 and IL-23, which play a role in the protection against mucosal candidiasis (Huppler et al, 2014) and other opportunistic infections (Heron & Elahi, 2017). In addition, Notch-1 signalling mediates oral epithelial cell differentiation (Casey et al, 2006) and regulates the activity of CD4+ T-cell responses by promoting cellular longevity (Helbig et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that HIV-1 infection is associated with alterations in the gut microbiome. These occur early in the course of infection, as a consequence of the depletion of CD4+ T cells in the intestinal mucosa, and are not fully restored with antiretroviral therapy (Brenchley, 2013;Heron & Elahi, 2017;Saxena et al, 2016;Zevin, McKinnon, Burgener, & Klatt, 2016). Whether similar changes occur in the oral microbiome are, as yet, unknown.…”
mentioning
confidence: 99%